A novel interstitial deletion of chromosome 2q21.1‐q23.3: Case report and literature review. Issue 4 (28th January 2020) - Almuzzaini, Bader; Alatwi, Nasser S.; Alsaif, Saif; Al Balwi, Mohammed A.
Abstract: Background: Interstitial deletions of 2q are rare. Those that have been reported show varying clinical manifestations according to the size of the deletion and the genomic region involved. Method and Results: We describe a preterm male harboring a novel interstitial deletion encompassing the 2q21.2‐q23.3 region of 2q, a deletion that has not been described previously. The patient had multiple congenital anomalies including agenesis of the corpus callosum, congenital cardiac defects, bilateral hydronephrosis, spontaneous intestinal perforation, hypospadias and cryptorchidism, sacral dimple and rocker‐bottom feet. Array comparative genomic hybridization (aCGH) analysis revealed a de novo >18 Mb deletion at 2q21.1–q23.3, a region that included (605802, 611472 and 604593) OMIM genes. Conclusion: To the best of our knowledge this is the first report of a de novo interstitial deletion at 2q21.1–q23.3 in which haploinsufficiency of dose‐sensitive genes is shown to contribute to the patient's phenotype. Abstract : Patient harboring a novel interstitial deletion encompassing 2q21.2‐q23.3 chromosomal region. Array revealed a de nova >18‐Mb deletion at 2q21.2‐q23.3. We thought that a haploinsufficiency genes may associated significantly contributed to patient manifestation.